Eucharist and offering - Stevenson, Kenneth W. (New York : Pueblo Pub, 1986)
In this book, Kenneth Stevenson explores the metaphor of sacrifice that found expression in the prayers and hymnody of the various eastern and western churches. He shows the development of the metaphor through the ages by applying the criteria of story, gift and response.
Future out of the past
Bibliography: p. 281-300
Includes indexes
Keywords: Lord's Supper -- Sacrifice -- History